LENGUAJE POLÍTICO Y GIRO PANHISPÁNICO EN EL PRIMER MANIFIESTO DEL MOVIMIENTO “POESÍA ANTE LA INCERTIDUMBRE” - MARTÍNEZ PÉRSICO, Marisa (Studia Universitatis Babeș-Bolyai Philologia, 2021)
Political Language and Reflections on the Concept of Canon from a Transatlantic Perspective in the First Manifesto of the Movement Poesía ante la incertidumbre. In this article I intend to examine the strengths of Panhispanic or Transatlantic Studies, which represent an appropriate line of research into and analysis of the current circumstances of literature written in Spanish, from a vantage point capable of observing the plurality of changes in the Hispanic-American poetics of twenty-first century works. First of all, I define what is traditionally understood as a literary canon and outline the theoretical support on which I rely to argue my point of view. Secondly, I add the notes of the critics who propose a Transatlantic literary analysis, that is, the ideas of Panhispanism, as a way of analyzing current poetic productions, which I exemplify with the Poetry Facing Uncertainty movement. REZUMAT. Limbaj politic și reflecții asupra conceptului de canon din perspectivă panhispanică în primul manifest al mișcării Poesía ante la incertidumbre. Acest articol își propune să reflecteze asupra coincidenței temporale între redactarea manifestului inițial al mișcării poetice transaltantice Poesía ante la incertidumbre și apariția mișcării 15M sau a indignaților în Spania, ambele având loc în mai 2011, ca fenomen care exemplifică suprapunerea dintre estetic și social. Coincidențele se evidențiază în mărcile intratextuale, discursive, din primul lor manifest ”Apărarea poeziei”, pe care-l vom analiza în acest articol. De asemenea, vom cerceta scopurile principale ale acesti grup, care este încă activ la zece ani de la fondarea sa, precum vocația programatică de a scrie o poezie cu caracter panhispanic. Cuvinte-cheie: canon, studii panhispanice, literatură transaltantică, poezie în spaniolă, Poesía ante la incertidumbre